A Comparative Study on Rendering of Expressive Meaning in the Main Register of “Jinling Prophecies” and the Twelve Songs in Hong Lou Meng - Xue, Wensi (American Journal of Humanities and Social Sciences, 2013)
“Jinling Prophecies” and the twelve songs in Hong Lou Meng are considered to be a dominating outline that echoes the former plots and starts the latter, and most importantly, hint the tragic fates of the twelve female characters. Grounded in the classification of lexical meaning by D﹒A﹒Cruse, the author of the paper uses textual analysis on lexical selection which Cao Xueqin had made in “Jinling Prophecies” and the twelve songs and has a comparative study on rendering of expressive meaning in two English versions from perspectives of culture, language, and psychology, examining to what extent the expressive meaning can be rendered and how much they have been rendered, in order to find proper criteria for rendering of expressive meaning in poetry translation. Moreover, here would be the first time the concealing psycho-information of Cao Xueqin and the main characters are analyzed as a research object on expressive meaning in translation studies, hoping to contribute a little to the translation practice.